Space‐Confined One‐Step Growth of 2D MoO2/MoS2 Vertical Heterostructures for Superior Hydrogen Evolution in Alkaline Electrolytes. Issue 32 (16th July 2022) - Wu, Qinke; Luo, Yuting; Xie, Ruikuan; Nong, Huiyu; Cai, Zhengyang; Tang, Lei; Tan, Junyang; Feng, Simin; Zhao, Shilong; Yu, Qiangmin; Lin, Junhao; Chai, Guoliang; et al.
Abstract: 2D material‐based heterostructures are constructed by stacking or spicing individual 2D layers to create an interface between them, which have exotic properties. Here, a new strategy for the in situ growth of large numbers of 2D heterostructures on the centimeter‐scale substrate is developed. In the method, large numbers of 2D MoS2, MoO2, or their heterostructures of MoO2 /MoS2 are controllably grown in the same setup by simply tuning the gap distance between metal precursor and growth substrate, which changes the concentration of metal precursors feed. A lateral force microscope is used first to identify the locations of each material in the heterostructures, which have MoO2 on the top of MoS2 . Noteworthy, the creation of a clean interface between atomic thin MoO2 (metallic) and MoS2 (semiconducting) results in a different electronic structure compared with pure MoO2 and MoS2 . Theoretical calculations show that the charge redistribution at such an interface results in an improved HER performance on the MoO2 /MoS2 heterostructures, showing an overpotential of 60 mV at 10 mA cm −2 and a Tafel slope of 47 mV dec −1 . This work reports a new strategy for the in situ growth of heterostructures on large‐scale substrates and provides platforms to exploit their applications. Abstract : Here, in situ growth of 2D MoO2 /MoS2 heterostructures on the centimeter‐scale substrate is shown. Noteworthy, the creation of a clean interface between atomic thin MoO2 (metallic) and MoS2 (semiconducting) results in a different electronic structure, which shows an improved HER performance with an overpotential of 60 mV at 10 mA cm −2 and a Tafel slope of 47 mV dec −1 .